Penggunaan Model Pembelajaran Jigsaw Dapat Meningkatkan Motivasi Dan Hasil Belajar Faktorisasi Prima Siswa Kelas VI SDN 3 Pule Semester I Tahun Pelajaran 2019/2020 - Ari Septanti (Universitas Sebelas Maret, 2020)
The purpose of this classroom action research is to determine the improvement of the learning process, increase motivation and learning outcomes using the Jigsaw Type Cooperative learning model. To achieve this goal, this research was designed in two cycles. The procedure in each cycle goes through several stages, namely planning, acting, observing and 4) reflecting on the follow-up.The improvement of the learning process is based on each cycle measured from the results of observations and tests of learning outcomes. Observational data are described, interpreted, then reflected to determine corrective actions in the next cycle. The action research conducted in two cycles showed that the average student motivation in the initial conditions was 64.41, the first cycle was 72, and the second cycle was 76.14. Learning outcomes in the initial conditions of 58.57 classical completeness level of 31.82%. In the first cycle, the average value of 67.61 classical completeness level of 58%. In the second cycle, the average value of 76.67 classical completeness level of 77%.Based on the results of the study, it can be concluded that the use of the Jigsaw learning model can increase the learning motivation of Prima Factorization of class VI students of SDN 3 Pule semester 1 of 2019/2020 by 11.73%.